2021
DOI: 10.1038/s41467-021-22480-x
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 regulates ribosome biogenesis in KRAS mutant non-small cell lung cancer

Abstract: SOD1 is known as the major cytoplasmic superoxide dismutase and an anticancer target. However, the role of SOD1 in cancer is not fully understood. Herein we describe the generation of an inducible Sod1 knockout in KRAS-driven NSCLC mouse model. Sod1 knockout markedly reduces tumor burden in vivo and blocks growth of KRAS mutant NSCLC cells in vitro. Intriguingly, SOD1 is enriched in the nucleus and notably in the nucleolus of NSCLC cells. The nuclear and nucleolar, not cytoplasmic, form of SOD1 is essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 56 publications
1
34
1
1
Order By: Relevance
“…Other biological process terms may also be linked to the tumorigenesis of lung cancer in their respective ways. For the cellular component cytosolic small ribosomal subunit, it has been shown to be abnormally regulated during the initiation and metastasis of lung cancer [ 114 ], corresponding with our results. As for the structural constituent of ribosome, in the same paper [ 114 ], authors also validated the specific role of ribosome during lung cancer tumorigenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Other biological process terms may also be linked to the tumorigenesis of lung cancer in their respective ways. For the cellular component cytosolic small ribosomal subunit, it has been shown to be abnormally regulated during the initiation and metastasis of lung cancer [ 114 ], corresponding with our results. As for the structural constituent of ribosome, in the same paper [ 114 ], authors also validated the specific role of ribosome during lung cancer tumorigenesis.…”
Section: Discussionsupporting
confidence: 90%
“…One biologically important ROS type in both homeostatic and stress situations is superoxide (Imlay, 2008), detoxified in part by superoxide dismutases (SODs). We have recently found that a fraction of mouse SOD1 localizes to the nucleolus and facilitates the generation of 60S ribosomal subunits in lung cancer cells (Wang et al, 2021). Thus, it appears that protecting pre-rRNA and the ribosome-building pathway from oxidative damage requires synergistic activities of different types of antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In inducible erbB2 (MMTV-iErbB2) and Wnt (MMTV-Wnt) transgene breast cancer models in mice, Sod1 knockout attenuates these oncogene-driven proliferations, but not normal proliferation of the mammary gland associated with pregnancy or other normal proliferative tissues, such as skin and gastro-intestinal tract epithelium [ 16 ]. Similarly, in a Kras/TP53 lung tumor-initiation model, tamoxifen-inducible Sod1 knockout significantly reduced lung tumor burdens due to inhibition of cancer cell proliferation [ 21 ]. In contrast, Sod1 knockout does not have discernible effect on proliferation of normal lung cells or other tissues [ 21 ].…”
Section: Role Of Sod1 In Normal Physiology and Diseasesmentioning
confidence: 99%
“…Similarly, in a Kras/TP53 lung tumor-initiation model, tamoxifen-inducible Sod1 knockout significantly reduced lung tumor burdens due to inhibition of cancer cell proliferation [ 21 ]. In contrast, Sod1 knockout does not have discernible effect on proliferation of normal lung cells or other tissues [ 21 ]. These observations document that SOD1 is an oncogene.…”
Section: Role Of Sod1 In Normal Physiology and Diseasesmentioning
confidence: 99%